Analisis Yurdis Putusan Nomor 101/Pid.B/2014/Pnrap tentang Perlindungan Hukum terhadap Anak sebagai Korban Tindak Pidana Perdagangan Orang - Gregorius Hari Saputra; Victor Imanuel Williamson Nalle (Universitas Muhammadiyah Yogyakarta, 2023)
Humans as creatures of God have the basic right to fulfill their rights and obligations which are known as human rights. These rights have the same position and apply in society as a manifestation of human character in society, nation and state. In its implementation, there are still many deviations that occur in the fulfillment of human rights. Human trafficking, especially carried out against children and women, is an example of a violation related to the fulfillment of human rights which is carried out by exploiting and turning humans into profitable commodities. Child trafficking is still a topic of discussion in the legal world because there are still many cases that occur in Indonesia involving child victims. The purpose of this article is to discuss further how the law in Indonesia protects every child from human trafficking. This research will use normative juridical research methods. From the research results, it can be concluded that regulations in Indonesia must be firmer and clearer to regulate and protect children from human trafficking and it is appropriate that existing regulations can provide a deterrent effect on perpetrators who carry out human trafficking of children. Juridical analysis carried out on court decision Number 101/Pid.B/2014/PN Rap revealed that the Judge had handed down a decision by sentencing the Defendant to 6 (six) years in prison and a fine of Rp. 120,000,000,- (one hundred and twenty million rupiah).